Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1177/0363546503262805
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Changes in the Hands and Fingers of Young, High-Level Climbers

Abstract: Intensive training and climbing lead to adaptive reactions; nevertheless, osteoarthrotic changes are rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 16 publications
5
59
1
1
Order By: Relevance
“…Chronic overuse injuries occur most often on the upper extremities at the elbow and the fingers [8,22,35]. As hand and finger injuries are the most common (table 7), many studies focus on these [9,24,[33][34][35][36][37][38]45]. Schöffl et al [35] found as the most common climbing injury the closed pulley rupture and the most common overuse injuries were epicondylitis and tenosynovitis of the finger flexor tendons.…”
Section: Injury Typementioning
confidence: 99%
See 1 more Smart Citation
“…Chronic overuse injuries occur most often on the upper extremities at the elbow and the fingers [8,22,35]. As hand and finger injuries are the most common (table 7), many studies focus on these [9,24,[33][34][35][36][37][38]45]. Schöffl et al [35] found as the most common climbing injury the closed pulley rupture and the most common overuse injuries were epicondylitis and tenosynovitis of the finger flexor tendons.…”
Section: Injury Typementioning
confidence: 99%
“…Modified from Schöffl et al[5] DAV = German Alpine Club; NACA = National Advisory Committee for Aeronautics, I = interview, P = prospective, Q = questionnaire, R = retrospective, E = physical examination. a NACA score graded by the authors according to the information given in the study.summits, making comparison with studies reporting injuries 1,000 h of sports performance difficult(table 4).Anatomical LocationTraditional and Sport Climbing Unfortunately, many scientific climbing papers present case studies or common hand injuries[9,24,[33][34][35][36][37][38] and are therefore not suitable for injury distribution analysis. So far, most research indicates that the upper extremity to be the most injured body regions in non-alpine rock climbing[8,19,22,24,25,27,39,40].…”
mentioning
confidence: 99%
“…[23] T›rman›c›l›k da el OA's› ile iliflkili bulunmufltur. [24] Ayr›ca, Çinliler'de çubukla yemek yemek gibi spesifik aktiviteler de el OA's› ile iliflkilidir. [25] …”
Section: Mekanik Yükunclassified
“…Many scientific climbing papers only present case studies or common hand injuries [17,19,30,41,48,54,55,[60][61][62][63] and are there- Table 1 The ten most frequent localization of climbing specific diagnoses 1/98-12/01 [61] n (%) Schöffl …”
Section: Injury Distributionmentioning
confidence: 99%